Trends in the Control Schemes for Bilateral Teleoperation with Time Delay - Zhu, Jiayi; He, Xiaochuan; Gueaieb, Wail (Université d'Ottawa | University of Ottawa, 2011)
In the last two decades, an increasing interest has been observed in the development of effective bilateral teleoperation systems. One of the biggest challenges encountered however is the presence of time delay, which can cause instability and poor transparency to the system. Researchers have been trying to tackle this problem from different angles and various control schemes have been proposed and tested. This paper aims to do an overview of those schemes and to compare them based on their assessment in order to give new researchers a summary of the current state of art. The schemes are divided into four main categories: passivity based, prediction based, sliding-mode control schemes and others. The comparison is based on transparency level, stability requirement, delay type, and delay range.
Keywords: bilateral teleoperation; time delay; delayed teleoperation; control scheme; passivity